The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1101/848887
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Discovery of an AKT Degrader with Prolonged Inhibition of Downstream Signaling

Abstract: The PI3K/AKT signaling cascade is one of the most commonly dysregulated pathways in cancer, with over half of tumors exhibiting aberrant AKT activation. Although potent small molecule AKT inhibitors have entered clinical trials, robust and durable therapeutic responses have not been observed. As an alternative strategy to target AKT, we report the development of INY-03-041, a pan-AKT degrader consisting of the ATP-competitive AKT inhibitor GDC-0068 conjugated to lenalidomide, a recruiter of the E3 ubiquitin li… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Recently, there has been the development of a new strategy for targeting kinases including AKT by co-opting proteasome-mediated degradation [10]. The AKT degraders were designed based on AKT inhibitors, but they possess additional chemical groups so that they can engage ubiquitin ligases leading to the degradation of target proteins through proteasomes [11][12][13][49][50][51][52]. A number of studies have found that this novel class of compounds is more effective than their parental AKT inhibitors in suppressing downstream signaling and reducing cancer cell growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, there has been the development of a new strategy for targeting kinases including AKT by co-opting proteasome-mediated degradation [10]. The AKT degraders were designed based on AKT inhibitors, but they possess additional chemical groups so that they can engage ubiquitin ligases leading to the degradation of target proteins through proteasomes [11][12][13][49][50][51][52]. A number of studies have found that this novel class of compounds is more effective than their parental AKT inhibitors in suppressing downstream signaling and reducing cancer cell growth.…”
Section: Discussionmentioning
confidence: 99%
“…In recent publications, You, et al developed new compounds that can recruit ubiquitin ligase E3 to downregulate AKT proteins through proteasome degradation [12,13]. We first compared the AKT degrader (INY-05-040) versus the clinically tested AKT catalytic inhibitor (GDC0068 or ipatasertib) in the human pancreatic cancer cell line PANC-1, low-passage patient-derived pancreatic cancer cells UM5, and a pancreatic cancer cell line derived from the KPC mouse model (Kras G12D ; Trp53 R172H ; Pdx1-Cre).…”
Section: Akt Degrader Is Superior To Akt Kinase Inhibitor In Slowing ...mentioning
confidence: 99%